Synthesis and characterization of a new thiazole Schiff base 5-bromo-2-hydroxybenzylidene-2-aminobenzothiazole and its complexes with Co(II), Cu(II) and Ni(II) - Saydam, S; Alkan, C (Polish Chemical Society, 2001)
A new ligand 5-bromo-2-hydroxybenzylidene-2-aminobenzothiazole has been synthesized from 2-aminobenzothiazole and 5-bromosalicylaldehyde by condensation in ethanol. Metal complexes of the ligand were prepared from chloride salts of Co(II), Cu(II), and Ni(II) in ethanol. Characterization of the ligand and its complexes were carried out by microanalyses, magnetic susceptibility measurements, FT-IR,C-13, H-1 NMR, and UV-Visible spectroscopy. It was suggested that two ligands with two water molecules coordinate to each metal atom by hydroxy oxygen and imino nitrogen to form high spin distorted octahedral complexes with Co(II), Ni(II) and Cu(II).
Keywords: 2-aminothiazole; thiazole; 5-bromosalicylaldehyde; Co(II); Ni(II); Cu(II) complex; synthesis